Syntheses and biological evaluation of new triazole-spirochromone conjugates as inhibitors of mycobacterium tuberculosis - Muthukrishnan, Murugan; Mujahid, Mohammad; Yogeeswari, P.; Sriram, D. (Tetrahedron Letters, 2011)
A series of novel 1,2,3-triazole fused spirochromone conjugates have been synthesized bearing both spirochromone moiety as well as a 1,2,3-triazole moiety. Some of the compounds have exhibited potential activity against Mycobacterium tuberculosis (virulent strain H37Rv). In particular 5e proved to be the most potent derivative exhibiting MIC = 0.78 mu g/mL. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular activity; Click chemistry; Mycobacterium tuberculosis; Spirochromones

Synthesis and antitubercular activity of amino alcohol fused spirochromone conjugates - Mujahid, Mohammad; Gonnade, Rajesh G.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, Murugan (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 21 new amino alcohol fused spirochromone conjugates have been synthesized, characterized with analytical data and evaluated their antimycobacterial activity against Mycobacterium tuberculosis (virulent strain H37Rv) in vitro. Some of the compounds exerted significant inhibition, in particular, compound 4f found to be the most potent derivative exhibiting MIC = 3.13 mu g/mL. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amino alcohol; Antitubercular activity; Mycobacterium tuberculosis; Spirochromones

Discovery of rimonabant and its potential analogues as anti-TB drug candidates - Gajbhiye, J. M.; More, Namita A.; Patil, Manoj D.; Ummanni, R.; Kotapalli, S. S.; Yogeeswari, P.; Sriram, D.; Masand, Vijay H. (Medicinal Chemistry Research, 2015)
Rimonabant and its analogues have been synthesized in moderate to good yields using a simple synthetic route. All the newly synthesized compounds were subjected to in vitro screening against M. tuberculosis and M. smegmatis. The most potent analogue JMG-14 exhibits MIC value of 3.13 compared to 3.25 and 50 A mu g/ml for ethambutol and pyrazinamide, respectively. The molecular docking reveals that pyrazole ring, number and position of halogen atoms play a crucial role in deciding interactions with MTCYP-121. These findings open up a new avenue in the search of potent anti-TB drugs with rimonabant and its novel analogue JMG-14 as lead molecules.
Keywords: Diaryl pyrazoles; H37Rv; MTCYP-121; Mycobacterium tuberculosis; Rimonabant; tuberculosis

Spirochromone-chalcone conjugates as antitubercular agents: synthesis, bio evaluation and molecular modeling studies - Mujahid, Mohammad; Perumal, Yogeeswari; Sriram, D.; Basavanag, U. M. V.; Dıaz-Cervantes, Erik; Cordoba-Bahena, Luis; Robles, Juvencio; Gonnade, Rajesh Ghanshyam; Karthikeyan, Muthukumarasamy; Vyas, Renu; Krishnan, M. Muthu (RSC Advances, 2015)
A new series of spirochromone annulated chalcone conjugates were synthesized and evaluated for their antitubercular activity against Mycobacterium tuberculosis H37Rv strain. These compounds were subjected to molecular modeling studies using docking and chemoinformatics based approaches. The docking simulations were performed against a range of known receptors for chalcone derived compounds to reveal MTB phosphotyrosine phosphatase B [MtbPtpB] protein as the most probable target based on the high binding affinity scores. Five compounds exhibit significant inhibition, showing minimum inhibitory concentration values i.e. MIC values ranging from 3.13–12.5 μg mL−1. Further analysis of the synthesized compounds with known and in-house developed chemoinformatics tools unequivocally established their potential as anti-tubercular compounds. QSAR modeling revealed a quantitative relationship between biological activities and frontier molecular orbital energies of synthesized compounds. The predictive model can be employed further for virtual screening of new compounds in this series.

Identification of potent chromone embedded [1,2,3]-triazoles as novel anti-tubercular agents - Nalla, Viswanadh; Shaikh, Aslam; Bapat, Sanket; Vyas, Renu; Karthikeyan, M.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, M. (Royal Society Open Science, 2018)
A series of 20 novel chromone embedded [1,2,3]-triazoles derivatives were synthesized via an easy and convenient synthetic procedure starting from 2-hydroxy acetophenone. The in vitro anti-mycobacterial evaluation studies carried out in this work reveal that seven compounds exhibit significant inhibition against Mycobacterium tuberculosis H37Rv strain with MIC in the range of 1.56-12.5 mu g ml(-1). Noticeably, compound 6s was the most potent compound in vitro with a MIC value of 1.56 mu g ml(-1). Molecular docking and chemoinformatics studies revealed that compound 6s displayed drug-like properties against the enoyl-acyl carrier protein reductase of M. tuberculosis further establishing its potential as a potent inhibitor.